Public expenditures on agriculture at subnational-levels and household-level agricultural outcomes in Nigeria - Takeshima, Hiroyuki; Smart, Jenny; Edeh, Hyacinth O.; Oyeyemi, Motunrayo; Balana, Bedru; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
Growing agriculture remains important for countries like Nigeria where, despite economic transformation at sectoral levels, a significant share of employment still originates from the agricultural sector. The question has continued to be debated of whether increasing Public Expenditures on Agriculture (PEA) is the way to grow agriculture. The needed evidence-base for this debate, while gradually growing, has remained insufficient in African countries, including Nigeria. This has been particularly the case as regards to evidence on the effects of PEA at household levels. This study attempted to partially fill this gap, using state and local government area (LGA)-level PEA figures and household data in Nigeria. The findings suggest that PEA has positive effects on household-level agricultural outcomes in various dimensions, including overall production levels, profits, access to public extension services or subsidized fertilizer, as well as private investments and, in some cases, agricultural mechanization. These patterns generally underscore the hypothesis that increasing direct support to the agricultural sector is likely to have greater effects on agricultural outcomes, compared to alternative strategies of developing agriculture indirectly through the support of other social-sectors like education, health, social safety-nets, among others. Increasing PEA by increasing the agricultural share of public expenditures (PE), while keeping the overall size of PE constant, is found to be particularly effective, compared to alternative approaches of increasing the overall size of PE while keeping agricultural share unchanged. Such patterns may suggest that Ricardian Equivalence partly holds. Furthermore, different agricultural outcomes are found to respond to PEA from different sources (e.g., LGA or State), and types (e.g., recurrent or capital spending). Enhancing research capacity to identify appropriate sources and types of PEA for particular agricultural outcomes remains important.